Retracing the restoration history of Viennese paintings in the Musée Napoléon (1809-1815) - Natalia Gustavson (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In 1809, a multitude of paintings belonging to the Austrian imperial collection was seized in Belvedere Palace in Vienna and brought to the Parisian Musée Napoléon. Those artworks have mainly been returned in 1815. Up to now, it remained unclear to what extent these paintings had been subjected to restoration treatments while in France. The following paper addresses the French treatment of a group of paintings today belonging to the Kunsthistorisches Museum in Vienna.